A tin-copper integrated electrode, a preparation method and a battery

CN123017897APending Publication Date: 2026-10-30XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510560833.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

这种体积膨胀和收缩的循环变化会导致锡负极材料发生结构崩塌,进而引起负极与集流体之间的界面脱落,形成电池容量衰减、循环寿命下降等问题

Benefits of technology

[0020](1)本发明所述的锡铜一体化电极具有铜簇体结构,增大了铜箔的表面粗糙度,同时铜簇体结构为锡的体积膨胀提供空间的同时限制了锡的过度膨胀,有利于电极的稳定性,在电池中具有更好的电化学稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017897A_ABST
    Figure CN123017897A_ABST
Patent Text Reader

Abstract

The application provides a tin-copper integrated electrode, a preparation method and a battery. A three-dimensional copper foil with a copper cluster structure on the surface is obtained by roughening and solidifying the surface of a copper foil. A tin-copper integrated electrode with tin wrapping the copper cluster structure is obtained by electrodeposition of tin on the surface of the three-dimensional copper foil. The copper cluster is perpendicular to the surface of the copper foil, the tin layer wraps the surface of each copper cluster structure, fills the gap between each copper cluster structure, and the thickness of the tin layer is lower than the height of the copper cluster structure. In this way, the interface bonding force between the active material tin and the current collector can be enhanced, the copper cluster structure on the surface of the three-dimensional copper foil can provide space for the volume expansion of tin during the battery cycle process, but limit the excessive expansion of tin, and the cycle stability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an integrated tin-copper electrode, its preparation method, and a battery, belonging to the field of electrochemical technology. Background Technology

[0002] With the rapid development of rechargeable battery technology, especially the widespread application of lithium-ion batteries and other high-energy-density batteries in portable electronic devices, electric vehicles, and energy storage systems, improving battery performance has become a key research objective. Against this backdrop, research on anode materials has become an important direction for improving the overall energy density and cycle stability of batteries. Traditional graphite anode materials, due to their relatively low specific capacity and cycle life limitations, are gradually failing to meet the demands of high-energy-density batteries. Therefore, researchers have turned their attention to anode materials with high specific capacity, such as tin (Sn), especially since tin's theoretical specific capacity is as high as 994 mAh / g, more than three times that of graphite, and is considered a promising alternative material.

[0003] However, despite tin's excellent theoretical specific capacity as an anode material, a serious problem it faces during charge and discharge is its significant volume expansion effect. Tin undergoes a volume expansion of up to approximately 300% during charging, followed by a sharp contraction during discharge. This cyclical expansion and contraction can lead to structural collapse in tin anode materials, causing interfacial detachment between the anode and current collector, resulting in battery capacity decay and reduced cycle life. Furthermore, volume expansion can also lead to irreversible reactions in the electrolyte, further accelerating battery aging. Therefore, suppressing the volume expansion of tin anode materials during charge and discharge has become one of the key challenges in improving the performance of tin-based anode materials. Summary of the Invention

[0004] In view of this, the present invention provides an improved method for preparing an integrated tin-copper electrode. The integrated tin-copper electrode prepared by the method has a greater interfacial bonding force with the current collector, a more sufficient space for volume expansion confinement, and better electrochemical cycle stability than conventional electrodes.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] In a first aspect, embodiments of the present invention provide a method for preparing an integrated tin-copper electrode, the method comprising:

[0007] Three-dimensional copper foil is obtained by depositing copper on the surface of copper foil through roughening and solidification; wherein, the three-dimensional copper foil is a copper foil with copper cluster structure grown on the surface, and the copper cluster is perpendicular to the surface of the copper foil;

[0008] A tin-copper integrated electrode is obtained by electrodepositing tin on the surface of a three-dimensional copper foil structure; wherein the tin layer wraps the surface of each copper cluster structure and fills the gaps between each copper cluster structure, and the thickness of the tin layer is less than the height of the copper cluster structure.

[0009] Preferably, the process of obtaining a three-dimensional copper foil by depositing copper on the surface of a copper foil through roughening and curing includes:

[0010] Prepare a roughening solution by dissolving 20–40 mL of concentrated sulfuric acid and 30–40 g of copper sulfate pentahydrate in 500 mL of deionized water; prepare a solidification solution by dissolving 10–20 mL of concentrated sulfuric acid and 125–150 g of copper sulfate pentahydrate in 500 mL of deionized water; place the copper foil in the roughening solution and set the cathode current density to 20–60 A / dm³. 2 The electrodeposition time was set to 1–6 s, and the electrodeposition temperature to 20–30 °C. The roughened copper foil was then placed in the curing solution, and the cathode current density was set to 15–25 A / dm³. 2 The electrodeposition time was set to 5–35 s and the electrodeposition temperature to 40–50 ℃ to obtain a three-dimensional copper foil.

[0011] Preferably, the method of obtaining an integrated tin-copper electrode by electrodepositing tin on the surface of a three-dimensional copper foil includes:

[0012] The electrodeposition tin solution was formulated with 0.2–0.3 M ammonium citrate and 0.04–0.06 M stannous chloride dihydrate. A three-dimensional copper foil was placed in the electrodeposition tin solution, and the cathode current density was set to 0.5–1.5 A / dm³. 2 The electrodeposition time is 100-200 s and the temperature is 20-30℃ to obtain an integrated tin-copper electrode.

[0013] Preferably, the surface roughness of the three-dimensional copper foil is between 1 and 1.5 μm.

[0014] Preferably, the thickness of the tin plating layer on the surface of the tin-copper integrated electrode is 0.5 to 1 μm.

[0015] Preferably, the surface of the tin-copper integrated electrode includes two or more metals or alloys selected from copper, tin, α-phase Cu6Sn5, and γ-phase Cu3Sn.

[0016] Secondly, embodiments of the present invention also provide a tin-copper integrated electrode, which is prepared by the tin-copper integrated electrode preparation method described in any one of the above claims.

[0017] Thirdly, embodiments of the present invention also provide a battery comprising the aforementioned tin-copper integrated electrode.

[0018] This invention provides an integrated tin-copper electrode, a preparation method, and a battery. The integrated tin-copper electrode has a three-dimensional copper cluster structure, and a tin layer on the surface of each copper cluster structure wraps the surface of each copper cluster structure and fills the gaps between each copper cluster structure. The thickness of the tin layer is less than the height of the copper cluster structure. The interface between the copper cluster surface and the tin forms a tin-copper alloy. The method for preparing the tin-copper integrated electrode includes the following steps: depositing copper on the surface of a copper foil through two-stage electrodeposition to obtain a three-dimensional copper foil; wherein, the three-dimensional copper foil is a copper foil with copper cluster structures grown on its surface, and the copper clusters are perpendicular to the surface of the copper foil; obtaining the tin-copper integrated electrode by electrodepositing tin on the surface of the three-dimensional copper foil; wherein, the tin layer wraps the surface of each copper cluster structure and fills the gap between each copper cluster structure, and the thickness of the tin layer is less than the height of the copper cluster structure; wherein, the battery includes the tin-copper integrated electrode, the tin on the surface of the tin-copper integrated electrode covers the surface of the copper clusters, and an alloy interface is formed between the tin and the copper clusters, which can increase the interfacial bonding force between the tin and the current collector, provide space for the volume expansion of tin while limiting the excessive expansion of tin, which is beneficial to improving the cycle stability of the battery.

[0019] The beneficial effects of this invention are:

[0020] (1) The tin-copper integrated electrode of the present invention has a copper cluster structure, which increases the surface roughness of the copper foil. At the same time, the copper cluster structure provides space for the volume expansion of tin while limiting the excessive expansion of tin, which is beneficial to the stability of the electrode and has better electrochemical stability in the battery.

[0021] (2) The tin-copper integrated electrode of the present invention is prepared by direct current electrodeposition, which is simple, reduces production costs, and is conducive to the industrial production of the product. Attached Figure Description

[0022] Figure 1 This is a SEM image of the three-dimensional copper foil and copper cluster structure provided in Embodiment 1 of the present invention;

[0023] Figure 2 This is a SEM image of the tin-copper integrated electrode provided in Embodiment 1 of the present invention;

[0024] Figure 3 This is a schematic diagram of the structure of an integrated tin-copper electrode provided in Embodiment 1 of the present invention;

[0025] Among them, copper foil substrate 1, copper cluster structure 2, and tin plating layer 3. Detailed Implementation

[0026] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention.

[0027] Example 1

[0028] A tin-copper integrated electrode prepared according to an embodiment of the present invention is as follows:

[0029] (1) Immerse the copper foil in a degreasing solution to clean the surface of the copper foil. Set the degreasing temperature to 60℃ and the degreasing time to 50s. Then place the degreased copper foil in an 8% dilute sulfuric acid solution for activation treatment and keep it for 20s to obtain activated copper foil;

[0030] (2) Dissolve 33 mL of concentrated sulfuric acid and 39 g of copper sulfate pentahydrate in 500 mL of deionized water to prepare a roughening solution; dissolve 15 mL of concentrated sulfuric acid and 135 g of copper sulfate pentahydrate in 500 mL of deionized water to prepare a solidification solution; place the activated copper foil in the roughening solution and set the cathode current density to 40 A / dm. 2 The electrodeposition time was set to 3 seconds and the electrodeposition temperature to 25°C. The roughened copper foil was placed in the curing solution, and the cathode current density was set to 20 A / dm³. 2 The electrodeposition time was set to 20s and the electrodeposition temperature to 45℃ to complete the copper electrodeposition process and obtain a three-dimensional copper foil.

[0031] (3) Dissolve 27g of ammonium citrate and 5g of stannous chloride dihydrate in 500mL of deionized water to prepare an electrodeposition tin solution; place the three-dimensional copper foil in the electrodeposition tin solution and set the cathode current density to 1A / dm. 2 A tin-copper integrated electrode was prepared by setting the electrodeposition time to 150 s and the electrodeposition temperature to 25 ℃.

[0032] (4) Apply 42 N / mm² to the tin-copper integrated electrode obtained above within an area of ​​10 mm × 20 mm. 2 After the adhesive tape fully adheres to the surface, it is peeled off. After peeling, the retention rate of the tin layer in the peeled area is observed under a microscope (retention rate = area of ​​tin layer detached after peeling / area of ​​adhesion area × 100%). The interfacial bonding force of the tin-copper integrated electrode is evaluated based on the retention rate of the tin layer in the peeled area.

[0033] (5) The lithium-ion battery with the tin-copper integrated electrode obtained above, i.e., with lithium metal as the counter electrode and the tin-copper integrated electrode as the working electrode, uses a Celgard-2500 series polypropylene separator and a 1M LiPF6 / EC∶DMC (1∶1) electrolyte; it is assembled using 2025 coin cells to prepare a lithium-ion battery. The cycle capacity and capacity retention of the battery are tested at different current densities.

[0034] Example 2

[0035] This invention provides an integrated tin-copper electrode prepared according to an embodiment of the invention. The specific implementation method is consistent with that of Embodiment 1, except that the roughening current density is adjusted to 30 A / dm in the "roughening and curing" step. 2 Conduct the experiment.

[0036] Example 3

[0037] This invention provides an integrated tin-copper electrode prepared according to an embodiment of the invention. The specific implementation method is consistent with that of Embodiment 1, except that the roughening current density is adjusted to 50 A / dm in the "roughening and curing" step. 2 Conduct the experiment.

[0038] Example 4

[0039] The tin-copper integrated electrode prepared for this embodiment of the invention is implemented in the same manner as in Embodiment 1, except that the curing time is adjusted to 10 seconds in the "roughening and curing" step.

[0040] Example 5

[0041] The tin-copper integrated electrode prepared for this embodiment of the invention is implemented in the same manner as in Embodiment 1, except that the curing time is adjusted to 30 seconds in the "roughening and curing" step.

[0042] Example 6

[0043] The tin-copper integrated electrode prepared for this embodiment of the invention is implemented in the same manner as in Embodiment 1, except that the deposition time in the "electrodeposition of tin" step is adjusted to 100s for the experiment.

[0044] Example 7

[0045] The tin-copper integrated electrode prepared for this embodiment of the invention is implemented in the same manner as in Embodiment 1, except that the deposition time in the "electrodeposition of tin" step is adjusted to 200s for the experiment.

[0046] Comparative Example 1

[0047] Compared to Example 1, the comparative example of this invention omits the roughening step, while other experimental conditions are the same as in Example 1.

[0048] Comparative Example 2

[0049] Compared to Example 1, the comparative example of this invention omits the curing step, while other experimental conditions are the same as in Example 1.

[0050]

[0051] Please refer to the table above, which summarizes the comparison between all embodiments and comparative examples in this invention. It can be seen from the table that:

[0052] (1) In Example 1, the coarsening current density was 40 A / dm. 2 The curing time was 20 s, and the resulting tin-copper integrated electrode was the optimal integrated electrode with 95% tin layer retention within the stripped area. After 20 cycles at 0.1C, the specific capacity was 505.04 mAh g. -1 After 50 cycles, the specific capacity was 501.63 mAh g. -1 After 100 cycles, the specific capacity is 240.85 mAh g. -1 ;

[0053] (2) By comparing Examples 1, 2 and 3, it can be seen that the roughening current density has a significant impact on the performance of the tin-copper integrated electrode. Reducing the roughening current density results in fewer copper cluster structures, a smaller contact area between the tin plating layer and the copper cluster structure, weaker physical anchoring effect, weakened interfacial bonding force, and a significantly reduced tin layer retention rate within the peeled area, leading to a significant decrease in the lithium battery cycle performance. Increasing the roughening current density results in a very dense copper cluster structure, a larger contact area between the tin plating layer and the copper cluster structure, stronger physical anchoring effect, stronger interfacial bonding force, and a higher tin layer retention rate within the peeled area. However, the space for tin volume expansion is reduced, and tin still experiences significant volume expansion during cycling, leading to a decrease in the lithium battery cycle performance.

[0054] (3) By comparing Examples 1, 4 and 5, it can be seen that the curing time has a significant impact on the performance of the tin-copper integrated electrode. When the curing time is reduced, the cured layer is thinner and more uneven, the copper cluster structure is unstable, the tin layer retention rate in the peeled area is significantly reduced, and the lithium battery cycle performance is significantly degraded. When the curing time is increased, the cured layer is too thick, the contact area between the tin plating layer and the copper cluster structure is reduced, the bonding force is weakened, the tin layer retention rate in the peeled area is reduced, and the lithium battery cycle performance is degraded.

[0055] (4) The comparison of Examples 1, 6 and 7 shows that the tin deposition time has a significant impact on the performance of the tin-copper integrated electrode. Reducing the tin deposition time results in a thinner tin plating layer, a smaller contact area between the tin plating layer and the copper cluster structure, weaker physical anchoring effect, weaker bonding force, and a significantly reduced tin layer retention rate within the peeled area, leading to a significant decrease in the cycle performance of the lithium battery. Increasing the tin deposition time results in an excessively thick tin plating layer that completely covers each copper cluster structure and fills the gaps between them. This results in a large contact area between the tin plating layer and the copper cluster structure, strong physical anchoring effect, strong interfacial bonding force, and a high tin layer retention rate within the peeled area. However, without reserving space to limit the volume expansion of tin, there is significant volume expansion of tin during cycling, leading to a decrease in the cycle performance of the lithium battery.

[0056] (4) By comparing Examples 1, 2, 3 and Comparative Example 1, it can be seen that the roughening step is crucial for the tin-copper integrated electrode. Without this step, a copper cluster structure cannot be formed on the copper foil, the bonding force between the tin plating layer and the copper foil is very weak, the tin layer retention rate within the stripped area is greatly reduced, the volume change of tin cannot be restricted during cycling, and the cycle performance of the lithium battery is greatly degraded.

[0057] (5) By comparing Examples 1, 4, 5 and Comparative Example 2, it can be seen that the curing step is very important for the tin-copper integrated electrode. Without this step, the copper cluster structure is very unstable. Most of the copper cluster structure will collapse when tin is plated. The bonding force between the tin plating layer and the copper foil is very weak. The tin layer retention rate in the stripped area is greatly reduced. The volume change of tin cannot be restricted during the cycle, and the cycle performance of the lithium battery is greatly reduced.

[0058] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and scope of the present invention are included within the scope of protection of the present invention.

Claims

1. A method for preparing an integrated tin-copper electrode, characterized in that, The method includes: Three-dimensional copper foil is obtained by depositing copper on the surface of copper foil through roughening and solidification; wherein, the three-dimensional copper foil is a copper foil with copper cluster structure grown on the surface, and the copper cluster structure is perpendicular to the surface of the copper foil. A tin-copper integrated electrode is obtained by electrodepositing tin on the surface of a three-dimensional copper foil structure; wherein the tin layer wraps the surface of each copper cluster structure and fills the gaps between each copper cluster structure, and the thickness of the tin layer is less than the height of the copper cluster structure.

2. The method for preparing the tin-copper integrated electrode according to claim 1, characterized in that, The process of depositing copper on the surface of a copper foil through roughening and curing to obtain a three-dimensional copper foil includes: Prepare a roughening solution by dissolving 20–40 mL of concentrated sulfuric acid and 30–40 g of copper sulfate pentahydrate in 500 mL of deionized water; prepare a solidification solution by dissolving 10–20 mL of concentrated sulfuric acid and 125–150 g of copper sulfate pentahydrate in 500 mL of deionized water; place the copper foil in the roughening solution and set the cathode current density to 20–60 A / dm³. 2 The electrodeposition time was set to 1–6 s, and the electrodeposition temperature to 20–30 °C. The roughened copper foil was then placed in the curing solution, and the cathode current density was set to 15–25 A / dm³. 2 The electrodeposition time was set to 5–35 s and the electrodeposition temperature to 40–50 ℃ to obtain a three-dimensional copper foil.

3. The method for preparing the tin-copper integrated electrode according to claim 1, characterized in that, The method of obtaining an integrated tin-copper electrode by electrodepositing tin on the surface of a three-dimensional copper foil includes: The electrodeposition tin solution was formulated with 0.2–0.3 M ammonium citrate and 0.04–0.06 M stannous chloride dihydrate. A three-dimensional copper foil was placed in the electrodeposition tin solution, and the cathode current density was set to 0.5–1.5 A / dm³. 2 The electrodeposition time is 100-200 s and the temperature is 20-30℃ to obtain an integrated tin-copper electrode.

4. The method for preparing the tin-copper integrated electrode according to claim 1, characterized in that, The surface roughness of the three-dimensional copper foil is 1 to 1.5 μm.

5. The method for preparing the tin-copper integrated electrode according to claim 1, characterized in that, The tin plating thickness on the surface of the tin-copper integrated electrode is 0.5–1 μm.

6. The method for preparing the tin-copper integrated electrode according to claim 1, characterized in that, The surface of the tin-copper integrated electrode includes two or more metals or alloys selected from copper, tin, α-phase Cu6Sn5, and γ-phase Cu3Sn.

7. A tin-copper integrated electrode, characterized in that, This includes preparation using the method for preparing the tin-copper integrated electrode according to any one of claims 1-6.

8. A battery, characterized in that, Includes the tin-copper integrated electrode as described in claim 7.